2020
DOI: 10.3389/fimmu.2020.01626
|View full text |Cite
|
Sign up to set email alerts
|

Overview: Systemic Inflammatory Response Derived From Lung Injury Caused by SARS-CoV-2 Infection Explains Severe Outcomes in COVID-19

Abstract: Most SARS-CoV2 infections will not develop into severe COVID-19. However, in some patients, lung infection leads to the activation of alveolar macrophages and lung epithelial cells that will release proinflammatory cytokines. IL-6, TNF, and IL-1β increase expression of cell adhesion molecules (CAMs) and VEGF, thereby increasing permeability of the lung endothelium and reducing barrier protection, allowing viral dissemination and infiltration of neutrophils and inflammatory monocytes. In the blood, these cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
153
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(167 citation statements)
references
References 105 publications
(145 reference statements)
6
153
0
8
Order By: Relevance
“…These conditions are characterized by increased permeability of lung capillaries and the entry of solutes and fluids into the alveolar lumen 70 (Box 3 ). In addition to increasing pulmonary oedema and facilitating leukocyte emigration, elevated vascular permeability may potentially facilitate SARS-CoV-2 dissemination to the circulation 71 .…”
Section: Leukocytes Recruited To Infected Lungsmentioning
confidence: 99%
See 1 more Smart Citation
“…These conditions are characterized by increased permeability of lung capillaries and the entry of solutes and fluids into the alveolar lumen 70 (Box 3 ). In addition to increasing pulmonary oedema and facilitating leukocyte emigration, elevated vascular permeability may potentially facilitate SARS-CoV-2 dissemination to the circulation 71 .…”
Section: Leukocytes Recruited To Infected Lungsmentioning
confidence: 99%
“…Reactive oxygen species, locally secreted by these aggregates or by entrapped neutrophils 70 , can also increase vascular permeability. In addition, in severe influenza virus infection and likely also in SARS-CoV-2 infection, VEGF 197 , tumour necrosis factor (TNF), IL-1β, NO and bradykinin, secreted by infected epithelial cells, by the endothelial cells lining the pulmonary vessels (primarily capillaries) and by both resident and recruited leukocytes 71 , may each increase lung vessel permeability and injury by reducing the integrity of VE-cadherin assemblies and driving endothelial contractility (reviewed in refs 23 , 198 ).…”
mentioning
confidence: 99%
“…Discussion SARS-CoV-2 infection could cause acute lung injury, and one of the important reasons is dysregulation of the immune system in the lung 8,9 that results in the release of a large number of in ammatory factors and forms "cytokine storm" 10 . In this study, we found that SARS-CoV-2 infection of macrophages and dendritic cells would promote the expression of abundant cytokines and chemokines by analyzing the GEO database (GSE155106).…”
Section: Sars-cov-2 N Protein Induces Mice Lung Injury Via Activatingmentioning
confidence: 99%
“…Therefore, the pathogenesis of SARS-CoV-2 is an urgent scienti c problem to be explored. SARS-CoV-2 infects human lung through the respiratory system and thus cause severe in ammatory responses 8,9 . Signi cant evidence demonstrated that a dysregulated innate immune response contributes to the clinical presentation of patients with severe COVID-19 10 .…”
mentioning
confidence: 99%
“…Also, increasing lung endothelium permeability and reducing barrier protection attracts more neutrophils to the infection site through endothelial penetration (Fig. 3b ) (Polidoro et al 2020 ). This inflammatory immune response dysregulation prevents adaptive immune response activation (Manjili et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%